1992
DOI: 10.1093/nar/20.8.1871
|View full text |Cite
|
Sign up to set email alerts
|

Cis-regulation of the L-type pyruvate kinase gene promoter by glucose, insulin and cyclic AMP

Abstract: The glucose/insulin response element of the L-pyruvate kinase gene is a perfect palindrome located from nt -168 to -144 with respect to the cap site. This element (L4) is partially homologous to MLTF binding sites. Its full efficiency requires cooperation with a contiguous binding site for HNF4, termed L3 and located from nt -145 to -125. In the presence of the L4 element contiguous to L3, cyclic AMP inhibits activity of the L-PK promoter while in its absence, or when the normal L4-L3 contiguity is modified, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
2

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 46 publications
7
190
2
Order By: Relevance
“…Transfection Experiments-The L4L3-119 L-PK/CAT and -119 L-PK/ CAT constructs have been described previously (25). Transfection was performed by lipofection using N- [1-(2,3-dioleoyloxy)propyl]-N,N,N-trimethylammonium methyl sulfate (DOTAP, Boehringer-Mannheim, Mannheim, Germany) according to the manufacturer instructions in cells cultured in glucose-free, serum-free medium for 3-4 h. Five g of CAT constructs and 2 g of pRSV-luciferase (or 1 g of pCMV-GLUT) were cotransfected in 60-mm plastic dishes (Falcon, Oxnard, CA) when cells were 60 -80% confluent.…”
Section: Methodsmentioning
confidence: 99%
“…Transfection Experiments-The L4L3-119 L-PK/CAT and -119 L-PK/ CAT constructs have been described previously (25). Transfection was performed by lipofection using N- [1-(2,3-dioleoyloxy)propyl]-N,N,N-trimethylammonium methyl sulfate (DOTAP, Boehringer-Mannheim, Mannheim, Germany) according to the manufacturer instructions in cells cultured in glucose-free, serum-free medium for 3-4 h. Five g of CAT constructs and 2 g of pRSV-luciferase (or 1 g of pCMV-GLUT) were cotransfected in 60-mm plastic dishes (Falcon, Oxnard, CA) when cells were 60 -80% confluent.…”
Section: Methodsmentioning
confidence: 99%
“…The most potent transcriptional stimulators are the liver-specific factors HNF-I and HNF-4. In transfection NF-I and USF in basal transcription is unclear [79,86,88,89]. Yamada et al [81] transfected hepatocytes in culture and proposed an activating function for USF, while Vaulont et al [80] could not find any function for USF in vitro.…”
Section: Tissue-specific Controlmentioning
confidence: 99%
“…The L5 sequence binds different proteins in liver and intestine [82]. Full understanding of their function awaits their purification since, depending on the experimental conditions, L5-binding factor displays activating [88] or inhibiting [81,82,89] properties.…”
Section: Tissue-specific Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments in transgenic mice have demonstrated that the sequences required for liver-specific and hormone-controlled expression reside between positions -183 and + 11. This region contains binding sites for the liverenriched factors HNFl and HNF4, and an element that, in cooperation with the HNF4-binding site, confers repression by CAMP and induction by insulin and glucose (Bergot et al 1992, Cuif et al 1992. Interestingly, the latter element shows no homology with a CRE.…”
Section: Expressionmentioning
confidence: 99%